A review of diapause and tolerance to extreme temperatures in dermestids (Coleoptera). (July 2016) - Wilches, D.M.; Laird, R.A.; Floate, K.D.; Fields, P.G.
Abstract: Numerous species in Family Dermestidae (Coleoptera) are important economic pests of stored goods of animal and vegetal origin, and museum specimens. Reliance on chemical methods for of control has led to the development of pesticide resistance and contamination of treated products with insecticide residues. To assess its practicality as an alternate method of control, we review the literature on the tolerance of dermestids to extreme hot and cold temperatures. The information for dermestid beetles on temperature tolerance is fragmentary, experimental methods are not standardized across studies, and most studies do not consider the role of acclimation and diapause. Difficulties in determining the diapause status of dermestid larvae may explain the lack of studies. The few studies that do examine these factors show that they can greatly increase tolerance to cold temperatures. The use of extreme temperatures will need to target the most tolerant life stage, which for dermestids at cold temperatures will potentially be the cold-acclimated individuals in diapause. The development of effective protocols will be facilitated by studies that clearly and completely describe experimental and statistical methods, consider factors (life-stage, acclimation, diapause) that increase tolerance to extreme temperatures, and assess the mortality at various temperatures to develop mathematical models. Highlights: Dermestids are important pests of stored products of animal or vegetal origin. Dermestid biology and tolerance to extreme temperatures is reviewed. Results indicate that control should target diapausing or cold-acclimated stages. More information is needed to optimize protocols for thermal control of dermestids.